Respuesta :
Note: As you may have unintentionally missed to add the expression, therefore, I am taking a sample expression that will still make sure to clear your concept and purpose. So, I will solve your query based on that sample expression.
Step-by-step explanation:
Considering the sample expression
[tex]2a + 3b + 3[/tex]
Substituting the values of [tex]a = -15[/tex] and [tex]b=-5[/tex] in [tex]2a + 3b + 3[/tex] to evaluate it.
As
[tex]2a + 3b + 3[/tex]
[tex]=2(-15) + 3(-5) + 3[/tex]
[tex]=(-30) + (-15) + 3[/tex]
[tex]=-30 -15 + 3[/tex]
[tex]=-42[/tex]
So, the value of the expression [tex]2a + 3b + 3[/tex] will be -42 if we substitute the values of [tex]a = -15[/tex] and [tex]b=-5[/tex] in it.
Keywords: algebraic expression
Learn more about algebraic expression from brainly.com/question/14500250
#learnwithBrainly